Oncologic outcomes of minimally invasive versus open radical hysterectomy for early stage cervical carcinoma and tumor size <2 cm: a systematic review and meta‐analysis. Issue 7 (July 2021) - Nasioudis, Dimitrios; Albright, Benjamin B; Ko, Emily M; Haggerty, Ashley F; Giuntoli, Robert L; Kim, Sarah H; Morgan, Mark A; Latif, Nawar A
ABSTRACT : Objective : To investigate the oncologic outcomes of patients with early‐stage cervical carcinoma and tumor size < 2 cm who underwent open or minimally invasive radical hysterectomy. Methods : The Pubmed/Medline, Embase, and Web‐of‐Science databases were queried from inception to January 2021 (PROSPERO CRD 42020207971). Observational studies reporting progression‐free survival and/or overall survival for patients who had open or minimally invasive radical hysterectomy for early‐stage cervical carcinoma and tumor size < 2 cm were selected. Level of statistical heterogeneity was evaluated with the I 2 statistic. A random‐effects model was used to compare progression and overall survival between the two groups and HR with 95% confidence intervals were calculated with the Der Simonian and Laird approach. Risk of bias and quality of included studies was assessed with the Newcastle‐Ottawa scale. Results : A total of 10 studies that met the inclusion criteria were included encompassing 4935 patients. Of these, 2394 (48.5%) patients had minimally invasive and 2541 (51.5%) patients had open radical hysterectomy; respectively. Patients who underwent minimally invasive hysterectomy had worse progression‐free survival than those who had open surgery (HR 1.68, 95% CI 1.20, 2.36, I 2 26%). Based on five studies, patients who had minimally invasive (n=1808) hysterectomy had a trend towards worse overall survival than those who had open surgery (n=1853) (HR 1.64, 95% CI 1.00 to 2.68, I 2 15%). Conclusion : Based on a systematic review of the literature and meta‐analysis of studies that control for confounders, for patients with cervical cancer and tumor size < 2 cm, minimally invasive radical hysterectomy was associated with worse progression‐free survival than laparotomy.